Working Capital Management and Financial Performance of Small and Medium Scale Enterprises in Kibuku District - Daniel Kirya (Uganda Christian University, 2025)
The study on Working Capital Management and Financial Performance of Small and Medium Enterprises in Kibuku District investigated how cash management, receivable management, and inventory management affect the financial performance of SMEs. The specific objectives were: to analyze the effect of cash management on financial performance, to examine the effect of receivable management on financial performance, and to assess the effect of inventory management on financial performance. Using a sample size of 63 respondents drawn from retail, service, and agro-processing SMEs, data were analyzed through descriptive statistics and regression models. Findings revealed that cash management significantly influenced financial performance with a coefficient of β = 0.153, p = 0.007, explaining 9.8% of the variation in SME performance. Similarly, receivable management showed a significant positive effect with β = 0.224, p = 0.015, accounting for 7.5% of the variation. In contrast, inventory management had no significant effect with β = 0.091, p = 0.169, contributing only 2.4% of the variation in financial performance. These results demonstrate that effective cash flow planning and receivable control are key drivers of profitability, liquidity, and resilience among SMEs in Kibuku, while inventory practices remain weak and underdeveloped. The study generally recommends that the government enhance financial literacy programs, expand access to affordable credit facilities, and provide infrastructural and technical support to SMEs. Strengthening cash and receivable practices while modernizing inventory management systems can enable SMEs in Kibuku District to improve resource utilization, achieve sustainable growth, and contribute more meaningfully to local economic development.